EPISTEMOLOGI SYARAḤ HADIS DI PERGURUAN TINGGI: DISKURSUS GENEALOGIS TERHADAP TRANSMISI DAN TRANSFORMASI METODE SYARAḤ HADIS DI INDONESIA - Egi Tanadi Taufik (Ushuluna: Jurnal Ilmu Ushuluddin, 2020)
The term syaraḥ and its education in Islamic universities have been misunderstood by contemporary scholars. The practice of syaraḥ has been interpreted by them in a narrower meaning, namely as an effort to elaborate Islamic classical sources in doctrinal and involution discourses. Thus these perceptions brought about stereotypes upon the development of the education of sharh in universities. This paper observes the development of Hadith studies in a diachronic reading through analyzing the position of sharh in the history of Hadith studies in Indonesia from the 16th century until present time, and from the formative to reformative era. The development and dynamic of sharh in history show that each Hadith scholar improving its construction idiosyncratically as an effort to answer current challenges by each context.